1999
DOI: 10.1002/(sici)1522-2683(19990101)20:1<204::aid-elps204>3.3.co;2-9
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous separation and enantioresolution of racemic local anesthetic drugs by capillary zone electrophoresis with Tween 20 and methyl-β-cyclodextrin as selectors, employing a double plug technique

Abstract: A new approach for simultaneous chiral and achiral separations by capillary zone electrophoresis is described. Two adjacent selector plugs, consisting of Tween 20 as an achiral and methyl-beta-cyclodextrin (CD) as a chiral selector, are employed and four related local anesthetics are used as model compounds. The principles of the partial filling technique, whereby the capillary is filled with the chiral selector solution followed by the micellar solution at different plug lengths and concentrations, prior to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The relationship between the plug length and migration time can be expressed by the following equation [42]:…”
Section: Rs(cond) = 2plap P (Vsl -Vs2)/ [Vsl Vs2 (Wb L + Wb2)] (13)mentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between the plug length and migration time can be expressed by the following equation [42]:…”
Section: Rs(cond) = 2plap P (Vsl -Vs2)/ [Vsl Vs2 (Wb L + Wb2)] (13)mentioning
confidence: 99%
“…In the first demonstration of this principle four local anaesthetics and their enantiomers were separated combining two adjacent selector plugs, consisting of Tween | 20 as an achiral and methyl-fi-cyclodextrin as a chiral selector [42]. In the first demonstration of this principle four local anaesthetics and their enantiomers were separated combining two adjacent selector plugs, consisting of Tween | 20 as an achiral and methyl-fi-cyclodextrin as a chiral selector [42].…”
Section: Simultaneous Separation and Enantioseparation Employing A Domentioning
confidence: 99%
“…Using carboxymethyl-β-cyclodextrin, Chankvetadze et al, demonstrated the potential of flow-counterbalanced capillary electrophoresis (FCCE) to increase selectivity for binary mixtures (38). The following applications using methylated cyclodextrin derivatives were reported: pressure supported CEC using capillaries packed with permethyl-β-cyclodextrin (38,40); separation of hexobarbital using a dual chiral recognition cyclodextrin derivatives (41); resolution of local anesthetic drugs using Tween 20 and methyl-β-cyclodextrin (42); nonaqueous separation of basic analytes using heptakis(2,3-dimethyl-6-sulfato)-β-cyclodextrin (43,44); determination of aspartic acid in biosamples (45); determination of salbutamol enantiomers and its application to dissolution samples (46); separation of numerous racemic drugs (47); and determination of binding constants between enantiomers of orciprenaline and methyl-β-cyclodextrin (48).…”
Section: Capillary Electrophoresismentioning
confidence: 99%
“…Different analytical methods have been developed for separation of enantiomers. Chiral separation by capillary electrophoresis (CE) using a variety of chiral selectors have been reported [7][8][9][10]. Among them cyclodextrins and their derivatives are the most frequently employed [11].…”
Section: Introductionmentioning
confidence: 99%